Sistem Informasi Tugas Akhir Program Studi Informatika - Mustianti Mustianti; Ida Bagus Ketut Widiartha; Moh Ali Albar (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
The thesis is one of the graduation requirements that students must take to obtain a bachelor's degree. Each student informatics study program who will carry out the Thesis will do several processes, including the process of registration of titles, guidance, registration of Thesis seminars, Examination and judiciary sessions. The thesis administration process is still running manually, where at the time of title registration, students must fill in the form of thesis title. After that, students will wait for the announcement to find out their supervisor as well as the registration of the Thesis Seminar, the examination, and the Judiciary sessions. Students must come directly to the office with the registration requirements. The process requires a long time so that thesis administration services become less effective. Therefore a website-based Thesis Information System was built which aims to facilitate the thesis administration process of Informatics study programs. Based on black box testing, this system was declared to have run well while testing using the MOS method showed that 95.34% of informatics student respondents, 99.33% of non-informatics student respondents, and 100% of lecturers and admin respondents agreed. Therefore this system is suitable for use. Keywords: Thesis, website-based, black box, MOS.